Impact of trap states on inductive phenomena in 30% InGaN/GaN MOW LED devices - Bozkurt, Kutsal; Ozdemir, Orhan; Kuruoglu, Neslihan Ayarcs; Alshehri, Bandar; Dogheche, Karim; Gaimard, Quentin; Ramdane, Abderrahim; Dogheche, Elhadj (IOP PUBLISHING LTD, 2019)
Investigation of structural quality (by x-ray diffraction) and analysis of defects and interfaces in epitaxial layers (by transmission electron microscopy (TEM)) have been performed on InGaN/GaN multiple quantum wells (MQWs) LED structure. Using energy dispersive x-ray analysis attached to the TEM system, 30% indium content in the InGaN well was measured. For electro-optic analysis, 30% in content InGaN/GaN MQWs LED in the p-i-n structure was analyzed through admittance spectroscopy and photo/electroluminescence (PL/EL) measurements. Electrical properties of the present LED structure were outlined first using AC admittance and DC current-voltage analyses. Trap level(s) in quantum wells (sub-bandgap) and the active layer of the p-i-n structure were defined by PL/EL measurement. Consumption of carriers through radiative recombination and trap filling/emptying processes (via these levels) competed with each others. This resulted in a non-equilibrium situation and originated from the inductive current. The analytically derived expression for the admittance in bipolar carrier injection was applied. It accounted for very good fits to the experimentally measured negative capacitance. The goodness of fits verified that recombination occurred faster than the trap filling/emptying process, causing the non-equilibrium situation.
Keywords: light emission diodes; LED; InGaN/GaN; LIGHT-EMITTING-DIODES; NEGATIVE CAPACITANCE; QUANTUM-WELL; VOLTAGE; BLUE; DEPENDENCE; ELECTRON; GREEN; Physics